Adolescent asthma management self-efficacy and responsibility: impact on asthma control and quality-of-life. (1st February 2023) - Sleath, Betsy; Carpenter, Delesha; Davis, Scott A.; Garcia, Nacire; Reuland, Daniel S.; Tudor, Gail; Loughlin, Ceila E.
Abstract: Objective: The purpose of this study was to investigate the extent to which adolescent asthma management self-efficacy, outcome expectations, and asthma responsibility were associated with asthma control and quality-of-life. Adolescent self-efficacy and outcome expectations are important components of social cognitive theory, which guided this research. Methods: English- and Spanish-speaking adolescents ages 11–17 with persistent asthma were recruited at four pediatric clinics. Adolescents were interviewed and parents completed questionnaires. Multiple linear regression was used to analyze the data. Results: Three hundred and fifty-nine adolescents were recruited. Older adolescent age, male gender, and higher adolescent asthma management self-efficacy were significantly associated with higher adolescent responsibility; outcome expectations were not significantly associated with responsibility. Adolescent ratings of their own responsibility were higher than parent ratings of their child's responsibility for almost all asthma management tasks. Adolescents with higher reported asthma management self-efficacy were significantly more likely to have better quality-of-life and controlled asthma. Adolescents with more positive outcome expectations were significantly more likely to have controlled asthma. Being Native American was associated with worse quality-of-life and asthma not being controlled. Being Black was associated with asthma not being controlled. Conclusions: Parents and providers should work to improve adolescent self-efficacy in managing their asthma because it is associated with asthma responsibility, asthma control, and quality-of-life. Providers need to especially work with Native American and Black adolescents to improve quality-of-life and asthma control.